Maternal psychosocial consequences of twins and multiple births following assisted and natural conception: a meta-analysis. Issue 1 (July 2016) - van den Akker, Olga; Postavaru, Gianina-Ioana; Purewal, Satvinder
Abstract: The aim of this meta-analysis is to provide new evidence on the effects on maternal health of multiple births due to assisted reproductive technology (ART). A bibliographic search was undertaken using PubMed, PsycINFO, CINAHL and Science Direct. Data extraction was completed using Cochrane Review recommendations, and the review was performed following PRISMA and MOOSE guidelines. Meta-analytic data were analysed using random effects models. Eight papers (2993 mothers) were included. Mothers of ART multiple births were significantly more likely to experience depression (standardized mean difference [SMD] d = 0.198, 95% CI 0.050 − 0.345, z = 2.623, P = 0.009; heterogeneity I 2 = 36.47%), and stress (SMD d = 0.177, 95% CI 0.049 − 0.305, P = 0.007; heterogeneity I 2 = 0.01%) than mothers of ART singletons. No difference in psychosocial distress (combined stress and depression) (SMD d = 0.371, 95% CI −0.153 − 0.895; I 2 = 86.962%, P = 0.001) or depression ( d = 0.152, 95% CI −0.179 − 0.483: z = 0.901; I 2 = 36.918%) were found between mothers of ART and naturally conceived multiple births. In conclusion, mothers of ART multiple births were significantly more likely to have depression and stress than mothers of ART singletons, but were no different from mothers of naturally conceived multiples.